(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2分解因式

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:12:23
(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2分解因式(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2分解因式(ax+by)^2+(ay-bx)^2+c^2x^2

(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2分解因式
(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2分解因式

(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2分解因式
(ax+by)^2+(ay-bx)^2+c^2x^2+c^2y^2
=a^2x^2+2abxy+b^2y^2+a^2y^2-2abxy+b^2x^2+c^2x^2+c^2y^2
=x^2(a^2+b^2+c^2)+y^2(a^2+b^2+c^2)
=(a^2+b^2+c^2)(x^2+y^2)

=a^2x^2+b^2y^2+a^2y^2+b^2x^2+c^2x^2+c^2y^2
=(a^2+b^2+c^2)x^2+(a^2+b^2+c^2)y^2
=(a^2+b^2+c^2)(x^2+y^2)

=a^2x^2+b^2y^2+a^2y^2+b^2x^2+c^2x^2+c^2y^2
=(a^2+b^2+c^2)x^2+(a^2+b^2+c^2)y^2
=(a^2+b^2+c^2)(x^2+y^2)